Reducción del riesgo de desastres tecnológico mediante el uso del sistema de manejo de riesgo de la Universidad Estatal de Bolívar en el complejo agroindustrial en el Laguacoto periodo 2017 - García Averos, Stalin Alexis (2017)
The presence of adverse events in the face of the influence of technological risk factors in the Agroindustrial Complex Laguacoto of the State University of Bolivar arises the need to reduce the risk of technological disasters by using the risk management system of the U.E.B. Once the subject was raised, the aim was to reduce the risk of technological disasters by using the procedure management system of U.E.B., identifying the types of possible risks prioritized for designing a fire procedures manual. In order to obtain information, research strategies were applied, which consisted of direct interviewing of personnel working in the complex, prioritization of risks through the characterization of said factors, projection of the area of incidence in case of disastrous events that have occurred. each of them has been interpreted. Among the main risks of technological disasters, with greater affectation was identified the fire, explosion and spill of the cauldron of thermal energy, fire, explosion and spill of the Electric generator and overload, short circuit and electric leakage of the electrical installations. To prioritize the main risks, the Areal Location Hazardous Atmospheres - ALOHA simulator was used to assess the levels of influence according to their impact on life, environment and property, in the event that Liquefied Petroleum Gas cylinders reach exploit or emit toxic clouds, thus harming workers, students, teachers, the environment and infrastructure that are in the range of influence. To provide the community with an adequate risk reduction system on the possible impact of an event with technological disasters, an operational, functional and organizational fire procedures manual was designed.